Introgression of teosinte branched1 gene from wild-progenitor enhances prolificacy in subtropically-adapted maize - Firoz Hossain; Rajkumar Uttamrao Zunjare; Rashmi Chhabra; Irum Gul; Amitkumar D. Kyada; Elizabeth Mathew; Ravindra K. Kasana; Nitish R. Prakash; Vinay Bhatt; Sunil Neelam; Vignesh Muthusamy (Planta, 2026)

Heritage Stones Through Ages and Civilizations: A Comparative Study of Western Ghats Laterite (India) and Tezontle Volcanic Scoria (Mexico) - Bobby P. Mathew; Carles Canet; Elizabeth Lozada-Amador; Gurmeet Kaur; Raymond A. Duraiswami; Elizabeth Castañeda-Bastida; Francisco O. Lagarda-García (Geoheritage, 2026)
A comparison is made between two IUGS Heritage Stones designated in 2024, Western Ghats Laterite (India) and Tezontle volcanic scoria (Mexico), to highlight their cultural impact across millennia and analyze a possible convergence in their use and symbolism. These stones originate from contrasting cultural settings and were generated through distinct geological processes and timescales. In both cases, they exhibit extensive, long-standing use in cultural heritage and are deeply rooted in local identity. Laterite is a residual product formed in situ through prolonged chemical weathering under humid tropical conditions, whereas tezontle is a highly vesicular volcanic scoria generated by Strombolian eruptions. From an aesthetic perspective, there is a significant coincidence based on their predominant reddish coloration and rough, matte surfaces. However, their resemblance in terms of mechanical properties, such as compressive strength and density, is notably lower; consequently, their technical applications differ in each case. A striking convergence exists in how architectural practices in both regions leveraged the favorable workability and aesthetic properties of these stones to achieve comparable results; both stones were paired with lighter materials to achieve visual contrast in intricate ornamentation set against the sober, dominant reddish-dark hue of the façades. This was particularly prominent during the Baroque period (16th–18th centuries), imprinting a distinct identity upon both regions through shared elements arising from the confluence of colonialism and deep-rooted indigenous cultures. Consequently, the use of these respective stones serves as an element of material continuity, acting as a tangible bridge between colonial influence and native heritage. The designation as an IUGS Heritage Stone is strengthened by the prior recognition of World Heritage properties featuring these stones, creating a synergy that enhances the connections between cultural and geoheritage. This joint recognition should foster cohesive conservation policies prioritizing original restoration materials, the protection of historical quarries, and the development of geotourism.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Exploratory profiling of microbial communities associated with tapping panel dryness in Hevea brasiliensis - Ann Tom; P. Sainamole Kurian; Shaji Philip; Deepu Mathew; Reshmy Vijayaraghavan; V. Sumbula; Minu Elizabeth Varkey (Archives of Microbiology, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Systemic Metabolites and Cytokines as Predictive Biomarkers of Metabolic Syndrome in Young Healthy Cohort: A Prospective Study - Reema George; Limi Elizabeth Mathew; Maya G. Pillai; Helen Antony (Indian Journal of Clinical Biochemistry, 2026)

Unravelling Ovarian Cancer: an analysis of the Influence of LRP1 and PAI1 Genetic Variations - R. B. Devi Krishna; Sneha Grace Mathews; Preet Agarwal; C. Elizabeth Rani; Nandini Krishnamurthy; Sanjana Murali; A. Lohitha Rani; Leena Dennis Joseph; Banukeerthana Rajasekaran; F. Andrea Mary (Biochemical Genetics, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Human second-trimester fetal liver-derived mesenchymal stromal cells are more effective than adult bone marrow MSCs for their superior growth kinetics, immunomodulatory, and osteogenic potential - Ashis Kumar; Sowmya Ramesh; Vignesh Kumar; Jiji Elizabeth Mathews; Vrisha Madhuri (Tissue and Cell, 2025)

Productivity Drives Leaf Mycobiome Diversity Patterns at Global and Continental Scales - Mathew A. Harris; Martin Kemler; Bernard Slippers; Nils Hassel; Joshua Tsamba; Watchara Arthan; Elizabeth A. Kellogg; Taylor AuBuchon‐Elder; Maria S. Vorontsova; Sally Archibald; Gareth P. Hempson; Caroline E. R. Lehmann; et al. (Global Ecology and Biogeography, 2025)
Aim Studies assessing large‐scale patterns of microbial diversity have predominantly focused on free‐living microorganisms, often failing to link observed patterns to established theories regarding the maintenance of global diversity patterns. We aimed to determine whether foliar fungi on two closely related grass hosts— Heteropogon contortus and Themeda triandra —display a commonly observed latitudinal gradient in species richness and determine whether host identity, energy (temperature and precipitation), climate seasonality, fire frequency and grass evolutionary history drive the observed patterns in species richness and composition. Location Paleotropical. Time Period Contemporary. Major Taxa Studied Foliar fungi. Methods Foliar fungal diversity was quantified from 201 leaf samples of T. triandra and H. contortus collected across the distributional range of these species. Mixed effects models were used to quantify patterns of diversity and their correlates among and within continents. Ordinations were used to assess drivers of composition. Results Foliar fungi displayed consistent latitudinal diversity gradients in richness. Energy was a strong driver of richness at inter‐continental and continental scales, while other factors had inconsistent impacts on richness among scales, hosts and guilds. Globally, richness was higher in regions of higher growing season temperatures and where hosts were present for longer periods. Composition was primarily structured by geographic region at the global scale, indicating that distance was a dominant driver of community composition. Within Australia, temperature and rainfall seasonality and the amount of growing season rainfall, were the dominant drivers of both richness and composition. Main Conclusions We find some support for the idea that foliar fungal species diversity is governed by the same factors as many macro‐organisms (energy availability and evolutionary history) at inter‐continental scales, but also that fungal diversity and composition in the highly seasonal continent of Australia were driven by factors that shape tropical grassy ecosystems, namely climate seasonality and fire.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

B7-H3 at the crossroads between tumor plasticity and colorectal cancer progression: a potential target for therapeutic intervention - Elizabeth Varghese; Samson Mathews Samuel; Aranka Brockmueller; Mehdi Shakibaei; Peter Kubatka; Dietrich Büsselberg (Cancer and Metastasis Reviews, 2024)
B7-H3 (B7 homology 3 protein) is an important transmembrane immunoregulatory protein expressed in immune cells, antigen-presenting cells, and tumor cells. Studies reveal a multifaceted role of B7-H3 in tumor progression by modulating various cancer hallmarks involving angiogenesis, immune evasion, and tumor microenvironment, and it is also a promising candidate for cancer immunotherapy. In colorectal cancer (CRC), B7-H3 has been associated with various aspects of disease progression, such as evasion of tumor immune surveillance, tumor-node metastasis, and poor prognosis. Strategies to block or interfere with B7-H3 in its immunological and non-immunological functions are under investigation. In this study, we explore the role of B7-H3 in tumor plasticity, emphasizing tumor glucose metabolism, angiogenesis, epithelial-mesenchymal transition, cancer stem cells, apoptosis, and changing immune signatures in the tumor immune landscape. We discuss how B7-H3-induced tumor plasticity contributes to immune evasion, metastasis, and therapy resistance. Furthermore, we delve into the most recent advancements in targeting B7-H3-based tumor immunotherapy as a potential approach to CRC treatment.

John squire and endothelial glycocalyx structure: an unfinished story - Kenton P. Arkill; C. Charles Michel; Elizabeth V. M. Rider; Elise A. Wood; Mathew O. Small; Jennifer L. E. Brown; Abigail L. Kinnaird (Journal of Muscle Research and Cell Motility, 2023)
John Squire did not only produce leading works in the muscle field, he also significantly contributed to the vascular permeability field by ultrastructural analysis of the endothelial glycocalyx. Presented here is a review of his involvement in the field by his main collaborator C.C. Michel and his last postdoctoral researcher KP Arkill. We end on a reinterpretation of his work that arguably links to our current understanding of endothelial glycocalyx structure and composition predicting 6 glycosaminoglycans fibres per syndecan core protein, only achieved in the endothelium by dimerization.

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Use of phospholipid fatty acid analysis as phenotypic biomarkers for soil health and the influence of management practices - Charlotte E. Norris; Mathew J.B. Swallow; Daniel Liptzin; Michael Cope; G. Mac Bean; Shannon B. Cappellazzi; Kelsey L.H. Greub; Elizabeth L. Rieke; Paul W. Tracy; Cristine L.S. Morgan; C. Wayne Honeycutt (Applied Soil Ecology, 2023)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

A Sensitive Spectrofluorimetric Method for Curcumin Analysis - Anne Boyina Sravani; Elizabeth Mary Mathew; Vivek Ghate; Shaila A Lewis (Journal of Fluorescence, 2022)
Curcumin (CUR), a natural polyphenolic compound extracted from the rhizomes of Curcuma longa , is used as a pharmaceutical agent, spice in food, and as a dye. Currently, CUR is being investigated for cancer treatment in Phase-II clinical trials. CUR also possesses excellent activities like anti-inflammatory, anti-microbial, and anti-oxidant, therefore quality control is crucial. The present research work was to develop a new, simple, validated and time-saving rapid 96-well plate spectrofluorimetric method for the determination of CUR. The developed method was compared with routinely used high performance liquid chromatography (HPLC) technique. The developed method were found to be linear in the concentration range of 15 to 3900 ng/mL with R 2 ≥ 0.9983 for spectrofluorimetric and 50-7500 ng/mL with R 2 ≥ 0.9999 for HPLC method. Accuracy, intraday and interday precision was adequate, with RSD lower than the suggested limits. The limits for the detection and the quantification of CUR were 7 and 15 ng/mL for spectrofluorimetric, and 25 and 50 ng/mL for HPLC respectively. The Bland-Altman analysis demonstrated the similarities between the two methods. The 96-well plate method was successfully applied to determine CUR in solid lipid nanoparticles (SLNs) and chitosan nanoparticles (Chi-NPs). The developed spectrofluorimetric method can hence serve as a possible replacement for the HPLC method for the quantification of CUR in healthcare and food products.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Flavonoids against the Warburg phenotype—concepts of predictive, preventive and personalised medicine to cut the Gordian knot of cancer cell metabolism - Marek Samec; Alena Liskova; Lenka Koklesova; Samson Mathews Samuel; Kevin Zhai; Constanze Buhrmann; Elizabeth Varghese; Mariam Abotaleb; Tawar Qaradakhi; Anthony Zulli; Martin Kello; Jan Mojzis; et al. (EPMA Journal, 2020)
The Warburg effect is characterised by increased glucose uptake and lactate secretion in cancer cells resulting from metabolic transformation in tumour tissue. The corresponding molecular pathways switch from oxidative phosphorylation to aerobic glycolysis, due to changes in glucose degradation mechanisms known as the ‘Warburg reprogramming’ of cancer cells. Key glycolytic enzymes, glucose transporters and transcription factors involved in the Warburg transformation are frequently dysregulated during carcinogenesis considered as promising diagnostic and prognostic markers as well as treatment targets. Flavonoids are molecules with pleiotropic activities. The metabolism-regulating anticancer effects of flavonoids are broadly demonstrated in preclinical studies. Flavonoids modulate key pathways involved in the Warburg phenotype including but not limited to PKM2, HK2, GLUT1 and HIF-1. The corresponding molecular mechanisms and clinical relevance of ‘anti-Warburg’ effects of flavonoids are discussed in this review article. The most prominent examples are provided for the potential application of targeted ‘anti-Warburg’ measures in cancer management. Individualised profiling and patient stratification are presented as powerful tools for implementing targeted ‘anti-Warburg’ measures in the context of predictive, preventive and personalised medicine.

Magnetic nanoparticles for hyperthermia in cancer treatment: an emerging tool - Jobin Jose; Rajesh Kumar; Seetha Harilal; Githa Elizabeth Mathew; Della Grace Thomas Parambi; Ankitha Prabhu; Md. Sahab Uddin; Lotfi Aleya; Hoon Kim; Bijo Mathew (Environmental Science and Pollution Research, 2020)

Red Emitting Hydroxybenzazole (HBX) Based Azo Dyes: Linear and Non Linear Optical Properties, Optical Limiting, Z Scan Analysis with DFT Assessments - Chaitannya W. Ghanavatkar; Virendra R. Mishra; Suryapratap Sharma; Elizabeth Mathew; Subramaniyan Chitrambalam; Isaac H. Joe; Sekar Nagaiyan Nethi (Journal of Fluorescence, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Corrigendum: Severe Continental-Scale Impacts of Climate Change Are Happening Now: Extreme Climate Events Impact Marine Habitat Forming Communities Along 45% of Australia's Coast - Russell C. Babcock; Rodrigo H. Bustamante; Elizabeth A. Fulton; Derek J. Fulton; Michael D. E. Haywood; Alistair James Hobday; Robert Kenyon; Richard James Matear; Eva E. Plagányi; Anthony J. Richardson; Mathew A. Vanderklift (Frontiers in Marine Science, 2019)

Severe Continental-Scale Impacts of Climate Change Are Happening Now: Extreme Climate Events Impact Marine Habitat Forming Communities Along 45% of Australia’s Coast - Russell C. Babcock; Rodrigo H. Bustamante; Elizabeth A. Fulton; Derek J. Fulton; Michael D. E. Haywood; Alistair James Hobday; Robert Kenyon; Richard James Matear; Eva E. Plagányi; Anthony J. Richardson; Mathew A. Vanderklift (Frontiers in Marine Science, 2019)

Reviewing microbial electrical systems and bacteriophage biocontrol as targeted novel treatments for reducing hydrogen sulfide emissions in urban sewer systems - Elizabeth R. Mathews; Dean Barnett; Steve Petrovski; Ashley E. Franks (Reviews in Environmental Science and Bio/Technology, 2018)

Indigenous arthropod natural enemies of the invasive brown marmorated stink bug in North America and Europe - Paul K. Abram; Kim A. Hoelmer; Angelita Acebes-Doria; Heather Andrews; Elizabeth H. Beers; J. Christopher Bergh; Ric Bessin; David Biddinger; Paul Botch; Matthew L. Buffington; Mary L. Cornelius; Elena Costi; et al. (Journal of Pest Science, 2017)

Humpback whales interfering when mammal‐eating killer whales attack other species: Mobbing behavior and interspecific altruism? - Robert L. Pitman; Volker B. Deecke; Christine M. Gabriele; Mridula Srinivasan; Nancy Black; Judith Denkinger; John W. Durban; Elizabeth A. Mathews; Dena R. Matkin; Janet L. Neilson; Alisa Schulman‐Janiger; Debra Shearwater; et al. (Marine Mammal Science, 2017)
Humpback whales ( Megaptera novaeangliae ) are known to interfere with attacking killer whales ( Orcinus orca ). To investigate why, we reviewed accounts of 115 interactions between them. Humpbacks initiated the majority of interactions (57% vs . 43%; n = 72), although the killer whales were almost exclusively mammal‐eating forms ( MEKW s, 95%) vs . fish‐eaters (5%; n = 108). When MEKW s approached humpbacks ( n = 27), they attacked 85% of the time and targeted only calves. When humpbacks approached killer whales ( n = 41), 93% were MEKW s, and ≥87% of them were attacking or feeding on prey at the time. When humpbacks interacted with attacking MEKW s, 11% of the prey were humpbacks and 89% comprised 10 other species, including three cetaceans, six pinnipeds, and one teleost fish. Approaching humpbacks often harassed attacking MEKW s (≥55% of 56 interactions), regardless of the prey species, which we argue was mobbing behavior. Humpback mobbing sometimes allowed MEKW prey, including nonhumpbacks, to escape. We suggest that humpbacks initially responded to vocalizations of attacking MEKW s without knowing the prey species targeted. Although reciprocity or kin selection might explain communal defense of conspecific calves, there was no apparent benefit to humpbacks continuing to interfere when other species were being attacked. Interspecific altruism, even if unintentional, could not be ruled out.

Anti-inflammatory potential of β-amyrin, a triterpenoid isolated from Costus igneus - Kripa Krishnan; Limi Elizabeth Mathew; N. R. Vijayalakshmi; A. Helen (Inflammopharmacology, 2014)

Synthesis and biological evaluation of novel pyrimidine-2(1H)-ones/thiones as potent anti-inflammatory and anticancer agents - Vachala Seekarajapuram Dinakaran; Divya Jacob; Jessy Elizabeth Mathew (Medicinal Chemistry Research, 2012)

Kuroshio pathways in a climatologically forced model - Elizabeth M. Douglass; Steven R. Jayne; Frank O. Bryan; Synte Peacock; Mathew Maltrud (Journal of Oceanography, 2012)

Effect of ethanol extract of Sphaeranthus indicus on cisplatin-induced nephrotoxicity in rats - Jessy Elizabeth Mathew; Alex Joseph; Keloth Srinivasan; Seekarajapuram Vachala Dinakaran; Anand Mantri; Vinit Movaliya (Natural Product Research, 2012)

Population growth and colonization of Steller sea lions in the Glacier Bay region of southeastern Alaska: 1970s–2009 - Elizabeth A. Mathews; Jamie N. Womble; Grey W. Pendleton; Lauri A. Jemison; John M. Maniscalco; Greg Streveler (Marine Mammal Science, 2011)
We estimated trends in numbers of Steller sea lions in the Glacier Bay region of the eastern population from the 1970s to 2009. We documented the colonization of several new haul‐outs and the transition of one haul‐out (Graves Rocks) to a rookery, assessed seasonal patterns in distribution, and compared counts from different observation platforms. Sea lions increased in the region by 8.2%/yr (95%CI = 6.4%–10.0%), with the most growth at South Marble Island in Glacier Bay (16.6%/yr, 1991–2009) and rapid growth in Cross Sound. Seasonal patterns in the distribution of sea lions were likely influenced by new breeding opportunities and the seasonal availability of prey. Factors that likely contributed to the exceptional growth include availability of new habitat following deglaciation, immigration, redistribution, decreases in mortality, and ecosystem‐level changes. The rapid increase in sea lion numbers in this region is of particular interest in light of dramatic declines in the western population and evidence that Steller sea lions from both the eastern and western populations colonized the Graves Rocks rookery. The colonization and rookery development in this dynamic area may signal the reversal of the reproductive isolation of the two populations.

Alterations to pre-pulse inhibition (PPI) in chronic cannabis users are secondary to sustained attention deficits - Kirsty Elizabeth Scholes; Mathew Thomas Martin-Iverson (Psychopharmacology, 2009)

Harbor seal ( Phoca vitulina richardii ) decline continues in the rapidly changing landscape of Glacier Bay National Park, Alaska 1992-2008 - Jamie N. Womble; Grey W. Pendleton; Elizabeth A. Mathews; Gail M. Blundell; Natalie M. Bool; Scott M. Gende (Marine Mammal Science, 2009)

Impact of partial steps and momentum advection schemes in a global ocean circulation model at eddy-permitting resolution - Bernard Barnier; Gurvan Madec; Thierry Penduff; Jean-Marc Molines; Anne-Marie Treguier; Julien Le Sommer; Aike Beckmann; Arne Biastoch; Claus Böning; Joachim Dengg; Corine Derval; Edmée Durand; et al. (Ocean Dynamics, 2009)

ENVIRONMENTAL FLUCTUATIONS INDUCE SCALE‐DEPENDENT COMPENSATION AND INCREASE STABILITY IN PLANKTON ECOSYSTEMS - Amy L. Downing; Bryan L. Brown; Elizabeth M. Perrin; Timothy H. Keitt; Mathew A. Leibold (Ecology, 2008)
The temporal stability of aggregate community and ecosystem properties is influenced by the variability of component populations, the interactions among populations, and the influence of environmental fluctuations on populations. Environmental fluctuations that enhance population variability are generally expected to destabilize community and ecosystem properties, but this will depend on the degree to which populations are synchronized in their dynamics. Here we use seminatural experimental ponds to show that reduced synchrony among zooplankton taxa increases the temporal stability of zooplankton density, abundance, and ecosystem productivity in fluctuating environments. However, asynchrony only occurs at long timescales (∼80‐day periods) and under recurring environmental perturbations. At shorter timescales (∼10‐day periods) and in constant environments, synchronous dynamics dominate. Our findings support recent theory indicating that compensatory dynamics can stabilize communities and ecosystems. They further indicate that environmental fluctuations can enhance the likelihood of long‐period asynchrony and thus stabilize community and ecosystem properties despite their short term destabilizing effects.

Characterization of a SEPT9 interacting protein, SEPT14, a novel testis-specific septin - Esther A. Peterson; Linda M. Kalikin; Jonathan D. Steels; Mathew P. Estey; William S. Trimble; Elizabeth M. Petty (Mammalian Genome, 2007)

Impact of partial steps and momentum advection schemes in a global ocean circulation model at eddy-permitting resolution - Barnier Bernard; Gurvan Madec; Thierry Penduff; Jean-Marc Molines; Anne-Marie Treguier; Julien Le Sommer; Aike Beckmann; Arne Biastoch; Claus Böning; Joachim Dengg; Corine Derval; Edmée Durand; et al. (Ocean Dynamics, 2006)

DECLINES IN HARBOR SEAL (PHOCA VITULINA) NUMBERS IN GLACIER BAY NATIONAL PARK, ALASKA, 1992–2002 - Elizabeth A. Mathews; Grey W. Pendleton (Marine Mammal Science, 2006)
Glacier Bay National Park had one of the largest breeding aggregations of harbor seals in Alaska, and it is functionally the only marine reserve for harbor seals in Alaska; yet, numbers of seals in the Bay are declining rapidly. Understanding why seals in Glacier Bay are declining may clarify their minimal habitat needs. We estimated population trends using models that controlled for environmental and observer‐related factors. In 1992, 6,200 seals were counted on icebergs in a tidewater glacial fjord and at terrestrial sites; by 2002 only 2,550 seals were counted at these same haul‐outs. Numbers of non‐pups in the glacial fjord declined by 6.6%/yr (−39%/8 yr) in June and by 9.6%/yr (−63%/11 yr) in August and at all other haul‐outs by 14.5%/yr (−75%/10 yr) during August. In the glacial fjord the number of pups remained steady from 1994 to 1999 and made up an increasing proportion of seals counted (5.4%/yr), and the proportion of pups peaked at 34%–36%. The rapid declines do not appear to be due to changes in seal behavior or redistribution. The declines reinforce genetic evidence that harbor seals in Glacier Bay are demographically isolated from other populations and indicate that current management stocks need to be redefined. Changes in Glacier Bay's ecosystem and population demographic data from the glacial fjord suggest that interspecific competition and predation are likely factors in the declines.

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)